Bimbingan Karir Menurut STIFIn Tes (Telaah STIFIn Tes Farid Poniman dan Relevansi Menurut Konsep Kefitrahan Manusia dalam Islam) - Hermi Pasmawati (Institut Agama Islam Negeri Bengkulu, 2019)
In the process or stages of career guidance can not be separated from the stages of career exploration. One of the things that needs to be explored from within an individual is basic characteristics. STIFIn Test is a test instrument that can reveal a person's basic abilities or intelligence from an early age. This study examines the relevance between the stages of the career guidance process as seen from the process of identifying the intelligence machine possessed through the process of scanning the fingerprints of the ten fingers with the direction of the chosen field or profession and their relevance to the concept of potential in Islam. The writing method uses literature review by comparing, analyzing andconnecting STIFIn theory theory studies with the stages and processes of career guidance. This study found the results of the scanning of the ten fingerprints which produced nine types of individual characteristics, used as a basis in the process of entering the study, choosing majors or study programs or scientific fields and professions in accordance with the intelligence machine they have. In Islam, humans who are born into the world are the most perfect creatures. Furthermore in the hadith also explained that humans are born in a state of nature. Some commentators interpret the word fitrah as latent potential or basic potential brought by humans from birth. From this explanation it is very relevant that basically humans have the basic potential or genetic potential that has been provided from birth, to be developed in carrying out their professions and careers.